Development of Scratch-Based Interactive Quiz Learning Media on Statistics to Enhance Students’ Learning Outcomes - Sekarsari, A'isyah; Karimah, Sayyidatul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Low student achievement in statistics is often attributed to the use of learning media that lack innovation and interactivity. This study aims to develop Scratch-based interactive quiz learning media and to examine its validity, practicality, and effectiveness in improving students’ learning outcomes. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved 28 students from Grade XI Health Analyst (experimental group) and 26 students from Grade XI Computer and Network Engineering 2 (control group). Research instruments included expert validation sheets, student response questionnaires, and learning achievement tests. Data were analyzed both qualitatively and quantitatively, including a t-test to evaluate effectiveness. The validation results reached a score of 80% (valid category), while student responses reached 78% (practical category). The t-test revealed a significant difference (p < 0.05) between the mean learning outcomes of the experimental group (88.29) and the control group (82.77), indicating that the developed media was effective in enhancing student achievement. These findings suggest that Scratch-based learning media has the potential to serve as an innovative alternative for teaching statistics and can be further developed for other topics by utilizing more complex Scratch features to strengthen learning interactivity.